Peirce Semiotic Analysis of the Representation Of Oligarchic Power in the Korean Drama Film the Healer - Septiana, Rizka (UI Scholars Hub, 2023)
This study uses an interpretive/constructive paradigm and a qualitative approach using semiotic methods in its discussion. The purpose of this study is to show how a Korean drama film becomes a medium of representation or picture of reality, especially regarding the oligarchic power in the democratic history of South Korea at that time. This study will focus more on signs that describe or show the activities of oligarchic power in the Korean drama film The Healer. By using triadic analysis of Charles Oligarchy's semiotics, namely objects, interpretants and representatives, the researchers found that the semiotics of oligarchic power in the Korean drama film The Healer is illustrated by the use of the word